Scissor lift with real-time self-adjustment ability based on variable gravity compensation mechanism. (2nd August 2016) - Takesue, Naoyuki; Komoda, Yosuke; Murayama, Hideyuki; Fujiwara, Kousyun; Fujimoto, Hideo
Abstract : Most robots involved in vertical movement against gravitation require actuators large enough to support their own weight. To improve the inherent safety of such robots against the large actuators and reduce their energy consumption, numerous gravity compensation mechanisms (GCMs) have been proposed. Our previous study proposed a variable GCM (VGCM) that uses two types of springs and can adjust the compensation force. In this paper, a VGCM-based scissor lift (pantograph lift) that uses three springs and a smaller actuator is proposed. A prototype is designed and fabricated, and the performance of the prototype is evaluated experimentally. The results demonstrate that the developed scissor lift meets the design specifications. In addition, a load estimator is established based on the dynamic model of the scissor lift. A real-time self-adjustment method that automatically changes the compensation force is proposed, and its effectiveness is verified. Graphical Abstract: